Evaluation of the heterotic potential for seed yield and its attributing traits in Indian mustard (Brassica juncea L.) - VR Akabari; N Sasidharan (Journal of Oilseed Brassica, 2026)
Heterotic potential for seed yield, and yield components in Indian mustard was studied using line × testeranalysis involving three lines, and twenty testers for fourteen characters including seed yield, its components,and quality characters. Number of crosses exhibiting significant positive heterosis, heterobeltiosis, and economicheterosis for seed yield per plant were 9, 4 and 3, respectively. Three crosses depicted significant positiveheterotic effect for seed yield per plant, viz., GM-2 x PYM-7, GM-3 x PAB-9511 and GM-3 x NUDH-45-1.Among these crosses, GM-2 x PYM-7, and GM-3 x PAB-9511 also exhibited significant and desirableheterotic effect for numbers of siliquae per plant, primary branches per plant and secondary branches perplant. Hence, could be further evaluated in heterosis breeding programme, and simultaneously advanced insegregating generations to obtain desirable segregants for the development of superior genotypes.